Evaluating the capacity of community health volunteers and factors affecting their implementation of community health strategy in Mogotio Sub-County, Baringo, Kenya - Samuel, Bartena Kimosop; Esilaba, Moses Otiati; Donde, Oscar Omondi (International Journal Of Community Medicine And Public Health, 2020)
Background: Community health volunteers (CHVs) play key role in the delivery of community health strategy. Mogotio Sub County has a total of thirty-two health facilities with nine established Community Units. However, the dissemination of information on community health strategy to household members is low or non-existence, probably due to poor training and facilitation of CHV and lack of awareness creation to local communities in the implementation of the programme. Methods: Cross-sectional study design was used to collect primary and secondary data through administration of questionnaires to selected respondents in three locations to assess the capacity of CHVs and factors affecting their implementation of community health strategy in Mogotio Sub-County, Baringo, Kenya. Results: The results indicated that 46%, 36% and 18% of the household respondents had primary, secondary and tertiary level of education respectively. More than 33% of household heads respondents were not employed and hence had no sustainable source of income. A big number of CHV had not attained all the required qualifications for proper implementation of community health strategy. Additionally, the CHVs experienced numerous challenges that affected the efficient implementation of community health strategy. Majority (52.2%) of the CHVs had attained secondary education, and (45%) were unemployed, 35 % were engaged in business and 20% earned their living by engaging in casual labor. Conclusion: The study revealed the need by the county government to strengthen the capacity of the CHVs through proper training and adequate financial support.